The Complete Book of 1960s Broadway Musicals - Dietz, Dan (Rowman & Littlefield Publishers, 2014)
While the 1960s may have been a decade of significant upheaval in America, it was also one of the richest periods in musical theatre history. Shows produced on Broadway during this time include such classics as Bye, Bye Birdie; Cabaret; Camelot; Hello Dolly!; Fiddler on the Roof; How to Succeed in Business without Really Trying; Oliver!; and Man of La Mancha. Performers such as Dick Van Dyke, Anthony Newley, Jerry Orbach, and Barbara Streisand made their marks, and other talents—such as Bob Fosse, John Kander, Fred Ebb, Alan Jay Lerner, Frederick Loewe, Jerome Robbins, and Stephen Sondheim—also contributed to shows. In The Complete Book of 1960s Broadway Musicals, Dan Dietz examines every musical and revue that opened on Broadway during the 1960s. In addition to providing details on every hit and flop, Dietz includes revivals and one-man and one-woman shows that centered on stars like Jack Benny, Maurice Chevalier, Marlene Dietrich, Danny Kaye, Yves Montand, and Lena Horne. Each entry consists of: Opening and closing dates Plot summaries Cast members Number of performances Names of all important personnel, including writers, composers, directors, choreographers, producers, and musical directors Musical numbers and the names of performers who introduced the songs Production data, including information about tryouts Source material Critical commentary Tony awards and nominations Details about London and other foreign productions In addition to entries for each production, the book offers numerous appendixes: a discography, film and television versions, published scripts, Gilbert and Sullivan operettas, and lists of productions by the New York City Center Light Opera Company, the New York City Opera Company, and the Music Theatre of Lincoln Center. A treasure trove of information,this significant resource will be of use to scholars, historians, and casual fans of one of the greatest decades in musical theatre history.